2010
DOI: 10.1038/ja.2010.135
|View full text |Cite
|
Sign up to set email alerts
|

Pentalenic acid is a shunt metabolite in the biosynthesis of the pentalenolactone family of metabolites: hydroxylation of 1-deoxypentalenic acid mediated by CYP105D7 (SAV_7469) of Streptomyces avermitilis

Abstract: Pentalenic acid (1) has been isolated from many Streptomyces sp. as a co-metabolite of the sesquiterpenoid antibiotic pentalenolactone and related natural products. We have previously reported the identification of a 13.4-kb gene cluster in the genome of Streptomyces avermitilis implicated in the biosynthesis of the pentalenolactone family of metabolites consisting of 13 open reading frames. Detailed molecular genetic and biochemical studies have revealed that at least seven genes are involved in the biosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…The in vivo formation of the epimeric epoxylactone 18 as a shunt metabolite is therefore most likely due to oxidation of the intermediate α-methylenelactone pentalenolactone E ( 15 ) by an oxygenase that is distinct from both PenD or PntD and that is encoded by a gene that is external to either the pen or pnt biosynthetic gene clusters (Scheme 5). In a similar manner, we have recently reported that the hydroxylation of the normal biosynthetic pathway intermediate 1-deoxypentalenic acid ( 5) to the commonly occurring shunt metabolite pentalenic acid ( 20 ) is catalyzed by CYP105D7, a typical heme-dependent monooxygenase that is encoded by the sav7469 gene, located in the 9.05-Mb S. avermitilis linear chromosome more than 5 Mb from the ptl biosynthetic gene cluster (77). …”
Section: Discussionmentioning
confidence: 79%
“…The in vivo formation of the epimeric epoxylactone 18 as a shunt metabolite is therefore most likely due to oxidation of the intermediate α-methylenelactone pentalenolactone E ( 15 ) by an oxygenase that is distinct from both PenD or PntD and that is encoded by a gene that is external to either the pen or pnt biosynthetic gene clusters (Scheme 5). In a similar manner, we have recently reported that the hydroxylation of the normal biosynthetic pathway intermediate 1-deoxypentalenic acid ( 5) to the commonly occurring shunt metabolite pentalenic acid ( 20 ) is catalyzed by CYP105D7, a typical heme-dependent monooxygenase that is encoded by the sav7469 gene, located in the 9.05-Mb S. avermitilis linear chromosome more than 5 Mb from the ptl biosynthetic gene cluster (77). …”
Section: Discussionmentioning
confidence: 79%
“…5 The responsible P450, CYP105D7 (SAV_7469) has been cloned and characterized from S. avermitilis . 27 Although the recently determined structure of CYP105D7 (PDB ID 4UBS) has two molecules of diclofenac, rather than the natural substrate 11 , bound in the active site, 28 alignment with the structure of PntM carrying bound pentalenolactone F ( 2 ) reveals that the binding region for the carboxylate of 11 lies on the wall of the active site cavity of CYP105D7 that is opposite to that established for carboxylate binding by PntM. Binding of 1-deoxypentalenic acid ( 11 ) to CYP105D7 could therefore readily be accommodated by a ca.…”
Section: Resultsmentioning
confidence: 99%
“…There are only a limited number of reports on k cat /K m values for P450s. Examples are CYP105D7 (0.0006 M Ϫ1 s Ϫ1 ) from Streptomyces avermitilis (38), which is involved in the biosynthesis of pentalenolactone, and CYP107L (2.3 M Ϫ1 s Ϫ1 ) from Streptomyces platensis (39), which hydroxylates terfenadine, a kind of antihistamine agent. Compared to these values, the k cat /K m value (5.6 M Ϫ1 s Ϫ1 ) of the CYP154C3-catalyzed hydroxylation of ⌬ 4 -androstene-3,17-dione seems to be in an appropriate range.…”
Section: Discussionmentioning
confidence: 99%